Harry Potter and the goblet of fire [videorecording (Blu-Ray)] - Radcliffe, Daniel, 1989-; Watson, Emma, 1990-; Grint, Rupert, 1988-; Branagh, Kenneth; Rickman, Alan; Smith, Maggie, 1934-; Coltrane, Robbie; Richardson, Miranda; Fiennes, Ralph; Oldman, Gary
Harry Potter is mysteriously selected to compete in the prestigious Triwizard Tournament. Meanwhile, supporters of the evil Lord Voldemort send out a shockwave of fear when their Dark Mark scorches the sky, signaling Voldemort's return to power.